Improving The Students' Pronunciation Mastery by Using Pop Songs on The Youtube Music Application: English - Henny Fitri Wahyuni; Masagus Firdaus; Hanni Yukamana (Journal of English Development, 2024)
One of the ways to avoid miscommunication is to pronounce the words correctly. Unfortunately, pronunciation is one of the English aspects that are difficult to learn and teach. The research’s objectives are to know and analyze how the YouTube Music application could improve the eighth grade students’ pronunciation mastery at SMP Negeri 56 Palembang and to find out the causes of the students’ pronunciation problems. It was Classroom Action Research (CAR) with 3 ways of collecting data i.e. test, observation, and questionnaire. It was conducted for class 8.5 at SMP Negeri 56 Palembang. The research reached the successful criteria in the third cycle i.e. 80% of the students reached the KKM. The results showed that by doing the drilling technique, asking the students to sing the song together in some groups, and choosing the appropriate songs e.g. the songs that are viral or happening in the pronunciation classroom activities, the student’s enthusiasm and pronunciation mastery got higher. The lack of exposure to English, the lack of motivation to study English pronunciation, and some English sounds that are hard to pronounce because students do not find them in their native, are the three causes of the students’ pronunciation problems.